Mapping the landscape of a decade: a bibliometric review of mobile assistive technology research for dyslexic children - Mariam Mohamad; Noratikah Abdullah; Mageswaran Sanmugam (Intelektual Pustaka Media Utama, 2026)
Dyslexia, a prevalent neurodevelopmental disorder affecting reading and writing skills, poses significant challenges to educational attainment. In recent years, mobile assistive technologies have emerged as promising tools to support dyslexic children in their journey. Despite the increasing focus on mobile assistive technology for dyslexic children, a comprehensive overview of the research landscape is lacking. The field is characterized by a proliferation of studies, diverse methodologies, and an expanding knowledge base. This bibliometric review leverages advanced analytical tools, with a primary focus on the VOSviewer software, to conduct a comprehensive analysis of the 53 literatures spanning from 2014 to 2024. A carefully curated dataset, comprising research articles sourced from reputable databases, forms the basis of the analysis. Anticipated outcomes include visually rich maps depicting the keyword co-occurrence patterns within the realm of mobile assistive technology for dyslexic children. We expect to identify key articles shaping the field, prominent clusters of research, and evolving trends. This bibliometric review aspires to contribute a panoramic view of the last decade's research landscape in mobile assistive technology for dyslexic children. The anticipated insights hold the potential to guide future research directions, technological innovations, and educational interventions, ultimately enhancing the support available to dyslexic children through mobile assistive technologies.